Growth Mechanism of ZnO Thin Films Grown by Spray Pyrolysis Using Diethylzinc Solution. Issue 4 (7th November 2017) - Imai, Masato; Watanabe, Marin; Tominaga, Himeka; Yoshino, Kenji; Ogomi, Yuhei; Shen, Qing; Toyoda, Taro; Minemoto, Takashi; Hayase, Shuzi
Abstract : Non‐doped ZnO thin films are deposited on glass by spray pyrolysis using Diethylzinc diluted with diisopropyl ether. The droplet impacts are observed and the structural properties of films are studied as deposition temperature dependence. The shape of a droplet impacts changes from a hemisphere to a flat plane with increasing the deposition temperature. The images of cross sectional transmittance electron microscopy show granular non‐crystalline for RT (room temperature) sample and columnar polycrystalline for 150 °C sample as shown on the right‐side. The growth mechanism of ZnO thin films is discussed by considering the relationship between the shape of droplet impacts and the morphology of the deposited films. Also, the presence of the crystal formed by precursor is suggested for the films deposited at lower temperature. Abstract : Cross sectional TEM images of deposited films. Deposition temperature: (a) RT, (b) 150 °C.